An insilico study of selected mannose derivatives against UropathogenicEscherichia colitargeting fimH adhesin protein - Chowdhury, Abhishek; Choudhury, Manabendra Dutta; Laskar, Monjur Ahmed (International Journal of Human and Health Sciences (IJHHS), 2022)
Urinary tract infections (UTI) caused primarily by uropathogenic Escherichia coli (UPEC) are indeed an extremely contagious disease that affects people all over the world. FimH is a major virulence component in UTI pathogenesis, and inhibiting FimH function can be an efficient means to disarm UPEC bacteria, as well as a crucial target in the development of non-antibiotic mediated UTI treatment options. The goal of this study was to identify phytochemicals in Cranberry and Bearberry plant parts and assess their pharmacological characteristics. A computational methodology was used to predict the pharmacological characteristics of such substances. Compounds with pharmacophores comparable to those of known fimH inhibitors were chosen. Following that, additional research was carried out to assess their drug similarity, inhibitory potential, and IC50 values.Thus, the present study reports few novel fimHinhibitors derived from the selected plant’sphytochemicals, and is significant owing to their therapeutic implication as a non-antibiotic mediated therapy for UTI. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 420-431